1994
DOI: 10.1063/1.1145195
|View full text |Cite
|
Sign up to set email alerts
|

A high sensitivity momentum dispersive multichannel electron momentum spectrometer for studies in experimental quantum chemistry

Abstract: Articles you may be interested inA high-sensitivity angle and energy dipersive multichannel electron momentum spectrometer with 2π angle range Rev. Sci. Instrum. 82, 033110 (2011); 10.1063/1.3568744 (e, 2e) electron momentum spectrometer with high sensitivity and high resolution Rev. Sci. Instrum. 76, 063103 (2005); 10.1063/1.1897668A high sensitivity electron momentum spectrometer with simultaneous detection in energy and momentum Rev.The design and characterization of a high sensitivity multichannel momentum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…However, a large finite cross section at low momentum has been clearly observed (Brunger et al 1994) in the Xe 4d measurement (figure 1). This phenomenon has been confirmed by a further measurement (also shown in figure 1) for Xe 4d (Zheng et al 1998) recently obtained at E = 1200 eV using a high-performance angledispersive multichannel (e, 2e) spectrometer (Todd et al 1994), under similar experimental conditions. The 'unexpected' significant 'turn up' of the cross section below p ∼ 1 au was reproduced by a distorted-wave Born approximation (DWBA) calculation (Brunger et al 1994) using a near Hartree-Fock limit basis set (Clementi and Roetti 1974).…”
Section: L224supporting
confidence: 78%
“…However, a large finite cross section at low momentum has been clearly observed (Brunger et al 1994) in the Xe 4d measurement (figure 1). This phenomenon has been confirmed by a further measurement (also shown in figure 1) for Xe 4d (Zheng et al 1998) recently obtained at E = 1200 eV using a high-performance angledispersive multichannel (e, 2e) spectrometer (Todd et al 1994), under similar experimental conditions. The 'unexpected' significant 'turn up' of the cross section below p ∼ 1 au was reproduced by a distorted-wave Born approximation (DWBA) calculation (Brunger et al 1994) using a near Hartree-Fock limit basis set (Clementi and Roetti 1974).…”
Section: L224supporting
confidence: 78%
“…Thereafter, Weigold et al [10] have introduced one-dimensional position-sensitive detectors (PSDs) for parallel measurements over a range of energies. Brion et al [11] have reported a momentum dispersive spectrometer. These spectrometers are either energy or momentum dispersive and can be roughly classified as the second generation (EMS-2).…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties have been significantly reduced by improvements in instrumentation. Recently reported multichannel EMS spectrometers have substantially improved the sensitivity over that of earlier single channel instruments…”
Section: Introductionmentioning
confidence: 99%